Namibia : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2018)
The paper assesses the stability of Namibia's financial system. Macrofinancial vulnerabilities have built up over a period of rapid economic growth in Namibia, and the financial cycle has now turned down. The sovereign debt/GDP ratio has nearly doubled since 2014 which has reinforced the already strong bank-sovereign link. The rapid rise in housing prices and household debt, banks' large exposure to mortgages, and banks reliance on wholesale funding are sources of concern. A major decline in real estate prices would adversely affect bank capital and profitability. Financial sector oversight has been strengthened significantly since the 2006 Financial System Assessment Program, but further upgrades are needed.